CHAOS BASED BLOCK ENCRYPTOR - SARIN, FARHANA (Universiti Teknologi PETRONAS, 2008)
This project is basically a block encryption to protect block of data. In this project we will propose encryption algorithm which offer less computational complexity and also provide securing data not only during transmission but also during storage. For this project, the studies focus on Advanced Encryption Standard (AES) and H-CES (Hybrid Chaotic Encryption Scheme) algorithms which are to be used in order to implement this project. The coding of encryption and decryption algorithms is created using C language. The coding compilation is using Borland C++ program. This report is the documentation about the work that has been carried out on the project. This report is divide into several parts which is the introduction, literature review, methodology, result and discussion and conclusion.